The Taxpayers Growth and Tax Receipts Relating to the Application of PP 23 of 2018 at KPP Pratama Denpasar Timur - S D A P P Satrianingrum; I D M Partika; I M Suarta (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
Due to less optimal of the application of PP 46 of 2013 makes government attempting to reform this rule by replacing PP 23 which came into force since 1 July 2018 by lowering the final tax rate to 0.5%. This rule is expected to be able to increase the growth of taxpayers and due to the decrease in tax rates will affect tax receipt. The purpose of this research is to determine the differences in taxpayer growth and tax receipt before and after the application of PP 23 of 2018 at KPP Pratama Denpasar Timur. This research method uses comparative with hypothesis testing using statistical tests with the Independent Sample T Test method for the taxpayer growth variable and using the Man Whitney U test method for the tax receipt variable. The results of the taxpayer growth analysis show a significant difference between the growth of taxpayers before and after the application of PP 23 of 2018 with an average increase of 0.05%. The results of the tax receipt analysis show that there is a significant difference between tax receipt before and after the application of PP 23 of 2018 with decrease tax receipt of 23%.